(untitled) (Al-Qamar, 2020)
Symbols are basically tools to deliver the creative poetic meaning. In the poems of Iqbal, there are a large number of symbols used to explain and emphasize on the poetic meaning and message. Most of the symbols used in the poetry of Iqbāl have religious background like Iblīs, Mullā etc. This article is aimed to focus the symbolic poetry of Iqbal. It will be helpful in approaching the symbolical poetics of Iqbal.